Genetic variability of colombian populations of Trypanosoma cruzi and three of Trypanosoma rangeli (1999)
ABSTRACT: This paper presents our study of genetic variability of Trypanosoma cruzi and Trypanosoma rangeli strains isolated from different Colombian biological hosts, using multilocus enzyme electrophoresis for 15 enzyme systems and electrophoretic analysis of kinetoplast DNA (kDNA) digested with EcoRI and Mspl endonucleases. Isoenzyme profiles were used to determine genotypes for each of the strains. Populations of T. cruzi and T. rangeli were found to have a polymorphic average of 86.7% and 26.7%, respectively. Schyzodeme analysis showed high variability for T. cruzi, since its genetic distance values were found to be greater than 50%, considerably higher than those previously reported for several T. cruzi strains from other countries. These results suggest that Colombian strains should be considered as genetically independent entities and are worth studying independently from each other to clearly establish their biological and clinical characteristics.